Mexican De-Democratization? Pandemic, Hyper-Presidentialism and Attempts to Rebuild a Dominant Party System - Petersen,German (Pontificia Universidad Católica de Chile. Instituto de Ciencia Política, 2021)
ABSTRACT As in almost the entire world, in Mexico 2020 was the year of the pandemic. The health and socioeconomic consequences of Covid-19 were devastating, severely impacting levels of equality and inclusiveness in the country. In terms of public contestation, hyper-presidentialism and the attempts of the governing party (Morena) to become dominant have eroded checks and balances and limited political plurality in the political system. Morena is building on the bases of the former hegemonic —the PRI— and the PRD, although it faces the hurdle of weak institutionalization — albeit within a party system that is also weak. Overall, the sum of these elements suggests a process of de-democratization in the country. The recent 2021 elections were a relative setback for Morena's attempts to become a dominant party at the federal level, particularly in the Chamber of Deputies, but Morena's political strength was strongly consolidated at the local level.